Relationship between shoulder pain and weight of shoulder bags in young women - Abdon, Ana Paula Vasconcellos (2018)
The present study aimed to assess the relationship between shoulder pain and weight of shoulder bags in young women. Cross-sectional study conducted with 316 women aged 18-35 years from February 2013 to July 2014. A questionnaire was used to collect demographic data and information on physical activity, sleeping habits, presence of pain and its characteristics, use of bags, and percentage of bag weight–body weight ratio (%bagweight). Pearson’s chi-squared test and Mann-Whitney test were used to check for associations between the dependent variable (presence of pain) and the independent variables, with a significance level of 5% (p<0.05). In all, 195 (61.7%) women complained of shoulder pain. These women carried heavier shoulder bags (p=0.01), weighing circa 4.02% of their body weight (p=0.050), and the pain was proportional to a higher bag weight (p=0.023) compared to the painless group. Lack of physical activity and inadequate sleep position influenced the occurrence of shoulder pain (p=0.008 and p=0.017, respectively). The weight of the shoulder bag represented a risk factor for the onset of shoulder pain and women should not carry bags weighing more than 4% of their body weight.